2013
DOI: 10.1177/1045389x12473377
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the piezoelectric hysteretic behavior on the vibration-based energy harvesting

Abstract: Vibration-based energy harvesting has received great attention over the last years. The evaluation of the power output of the energy harvesters for different excitation frequencies and amplitudes of vibration has an important role in the design of the devices. In this regard, a wide range of nonlinear effects is observed having considerable influence on the generated power. The main goal of this contribution is to investigate the effect of the piezoelectric hysteretic behavior on the vibration-based energy har… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…This larger displacement causes vibrations in the piezoceramic material, allowing for a higher average power, considering the parameters adopted (See Table 1). Another aspect associated with the piezoceramic material is defined by [40][41][42][43][44][45][46][47][48][49][50][51][52][53], which establishes that changes observed in the hysteresis curves can characterize hard-type piezoceramic materials, which have a piezoelectric constant with low values, or soft-type piezoceramic materials with high piezoelectric constants.…”
Section: Parametermentioning
confidence: 99%
See 1 more Smart Citation
“…This larger displacement causes vibrations in the piezoceramic material, allowing for a higher average power, considering the parameters adopted (See Table 1). Another aspect associated with the piezoceramic material is defined by [40][41][42][43][44][45][46][47][48][49][50][51][52][53], which establishes that changes observed in the hysteresis curves can characterize hard-type piezoceramic materials, which have a piezoelectric constant with low values, or soft-type piezoceramic materials with high piezoelectric constants.…”
Section: Parametermentioning
confidence: 99%
“…However, for values of q4→1.0 there is a larger region for Pavg values, as we can see in Figure 5a,b We observed a significant change in the power of the system with the change in the exponent of the fractional derivative, because, for the application of the fractional operator in the system of Equation ( 7) the non-linearity of hysteresis depends on the rate and asymmetry of the piezoelectric actuators. According to [52,53], it states that the model with the classic Bouc-Wen damping is only efficient for the description of symmetric and rate independent hysteresis, and the model containing the fractional operator is dedicated to characterizing the asymmetric and rate-dependent behavior hysteresis. Therefore, we analyzed the dynamic behavior on the fractional parameter of the operator applied in this damping.…”
Section: Parametermentioning
confidence: 99%
“…Experimental tests showed a good agreement with the numerical results. Silva et al [26] investigated the hysteretic behavior of piezoelectric coupling, comparing the results with linear models. The results suggested that there is an optimum hysteretic behavior that can increase the harvested power output of energy harvesting systems.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of the power generated by the harvesting system suggests that nonlinear effects have considerable influence on the results [7]. Silva et al [11] investigated the effect of hysteretic behavior of piezoelectric coupling, comparing results with linear and nonlinear models, suggesting that there is an optimum hysteretic behavior that increases the power output of the energy harvesters.…”
Section: Introductionmentioning
confidence: 99%